Analysis of load factor and dwell time of buses in EDSA - Rentoy, Tom Mari Jandel C.
Dwell time is an important component in analyzing a bus transit system. It is necessary to study the behavior of buses in bus stops to be able to attain traffic simulations, and travel time and headway computations accurate to reality of the transit. Distinct behaviors of buses in EDSA are bus stop skipping and waiting for more passengers in bus stops. This study aims to quantify the probability of buses entering a bus stop using load factor and to determine the contribution of waiting time to the overall dwell time of the bus. Load factor and dwell time were tested for distributions most fit. Dwell time was analyzed according to bus stop positions and constraints. Passenger volume and departure rate were also derived from the data gathered. Data on load factor and dwell time of buses plying EDSA Magallanes to EDSA Kamuning, both northbound and southbound, were collected and analyzed using statistical methods of distribution fitling, regression and comparison of means. Results show that probability of entry of a bus onto a bus stop can be estimated using load factor, and waiting time contributes a large constant fraction of dwell time. Load factor followed a normal distribution. While, dwell time followed a log normal distribution.